Risking development by prioritizing the possession of firearms in Brazil: development is not achieved by arming the population! - Araújo, Gustavo Cunha; Paula de Oliveira, Deyla (Advances in Social Sciences Research Journal, 2019)
The information in this article problematizes and broadens the debate on the importance of science to the development of Brazil, which is currently in crisis due to cuts in research investments in the country, making it impossible for scientists to continue carrying out ground-breaking research. We argue that this is due to two main factors: the approval of the Constitutional Amendment Project no. 55/2016, popularly known as the “death PEC,” which freezes public investments for twenty years and heightens the precariousness of education, health, science, security, and other sectors key to the country’s development along with the lack of interest in investing in national science by President Jair Bolsonaro who, among other things, prioritizes the possession of firearms as well as relaxation in the control of pesticides, which can further increase deforestation and deteriorate Brazil’s environment. The development of a nation is dependent on many factors such as investment in health, education, public safety as well as science, technology, and innovation. Although Brazil is a country with enormous potential for economic development and international research, these areas have been neglected by the current government. This article analyzes the possession of firearms in Brazil as a means of inhibiting the country’s development. It concludes that investing in the above-mentioned areas can reduce violence and poverty among other problems that are present in countries where governments invest little in such crucial sectors.